Social-scientific modelling supporting theory development: A model of socioepidemiology of success in top-level sport - Pitsch, W. (International Journal of Computer Science in Sport, 2003)
In recent past, the connection between aspects of top level athletes` careers and success in top-level sport range was focussed by a sociological based theory of training in sports. Several studies showed, that simply structured connections between training in top level sports and success are far from being able to explain the emergence of success in sport in collectives from processes of individual top level athletes` careers. Especially the discontinuities in long during ingates of sport careers (e.g. Güllich et al. 2001) have led to the development of a "socioepidemiology of athletic success" which tries to derive the success a top level athlete reaches at the climax of his or her career from the fact, that these athletes missed career-terminating critical events in other segments of life (e.g. school). Basing on this first draft, an actor based divided intelligence-model was defined in order to explain effects in collectives from individual data. To do this, it was necessary to integrate social aspects, affecting training and careers in sport and several biological aspects of aging, affecting training and careers as well. This led to an interdisciplinary character of the model as well as to the necessity to extend instruments of social-scientific modelling.